(3GdWQQ GdehVhYI Ydi GdhKGFb GdeLehYIs - (3CHh eMeO gGQhf Hf CMeO Hf LYaQ GdfaRj GdTGWHjs
(3ChdgG (B:s
(3GdMeO ddg WQI (B: (3bGd (B: (3GHf QTO QMeg Gddg JYGdi eGd GdCHf dGjNdh ef CQHYI ChLg s
(3BNQgG (B:s
(3hcKQI GdKef hbdJg hCbUi Pdc TgQ , hdG GOQi ajeG hQGA Pdc JCNjQ Cbd GdKef Ch cKQJg , Je cJGH GdWQQ GdehVhYI Ydi GdhKGFb GdeLehYI HMhd Gddg hbhJg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3eOQjO (B(54/1) s
Keywords: (3Gdabg GdeGdcjs